Introducing a change in hospital policy using FMEA methodology as a tool to reduce patient hazards. Issue 1 (December 2016) - Ofek, Fanny; Magnezi, Racheli; Kurzweil, Yaffa; Gazit, Inbal; Berkovitch, Sofia; Tal, Orna
Abstract Background Intravenous potassium chloride (IV KCl) solutions are widely used in hospitals for treatment of hypokalemia. As ampoules of concentrated KCL must be diluted before use, critical incidents have been associated with its preparation and administration. Currently, we have introduced ready-to-use diluted KCl infusion solutions to minimize the use of high-alert concentrated KCl. Since this process may be associated with considerable risks, we embraced a proactive hazard analysis as a tool to implement a change in high-alert drug usage in a hospital setting. Methods Failure mode and effect analysis (FMEA) is a systematic tool to analyze and identify risks in system operations. We used FMEA to examine the hazards associated with the implementation of the ready-to-use solutions. A multidisciplinary team analyzed the risks by identifying failure modes, conducting a hazard analysis and calculating the criticality index (CI) for each failure mode. A 1-day survey was performed as an evaluation step after a trial run period of approximately 4 months. Results Six major possible risks were identified. The most severe risks were prioritized and specific recommendations were formulated. Out of 28 patients receiving IV KCl on the day of the survey, 22 received the ready-to-use solutions and 6 received the concentrated solutions as instructed. Only 1 patient received inappropriate ready-to-use KCl. Conclusions Using the FMEA tool in our study has proven once again that by creating a gradient of severity of potential vulnerable elements, we are able to proactively promote safer and more efficient processes in health care systems. This article presents a utilization of this method for implementing a change in hospital policy regarding the routine use of IV KCl.